Increasing Antimicrobial Resistance of Vibrio cholerae O1 Biotype El Tor Strains Isolated in a Tertiary-care Centre in India - Mandal, Jharna; KP, Dinoop; Parija, Subhash Chandra (Journal of Health, Population and Nutrition, 2012)
The antimicrobial susceptibility patterns are on constant change with the recent emergence of multidrugresistant strains of most bacteria. Results of recent studies in India showed that most isolates of Vibrio cholerae O1 were resistant to the commonly-used antibiotics. The study was conducted to determine the antibiotic susceptibility patterns of V. cholerae O1 isolated during 2008-2010 at the hospital of the Jawaharlal Nehru Institute of Post Graduate Medical Education and Research, Puducherry, India. In total, 154 strains of V. cholerae O1 from 2,658 stool specimens were reported during January 2008December 201034 in 2008, 2 in 2009, and 118 in 2010. The isolates of V. cholerae O1 were subjected to antimicrobial susceptibility testing using the Kirby-Bauer method. The antibiotic disks tested were tetracycline (30 ?g), furazolidone (100 ?g), ampicillin (10 ?g), ceftriaxone (30 ?g), and ciprofloxacin (5 ?g). Escherichia coli ATCC 25922 was used as the control organism. The minimum inhibitory concentrations (MICs) of ceftriaxone, ciprofloxacin, and tetracycline were determined using the agar dilution method for all the strains. The E-test method was used for the strains which had either intermediate resistance or were resistant to the antibiotics by the agar dilution method. The results of the agar dilution corroborated the results of the E-test. The MIC of ceftriaxone in 151 strains was <2 ?g/mL while it was 16 ?g/mL in three strains; the latter three strains were resistant to ceftriaxone by the disc-diffusion test. The MIC of ciprofloxacin in 150 strains was <0.5 ?g/mL while the MIC of tetracycline was <1 ?g/mL. In the remaining four strains, the MIC of tetracycline was >32 ?g/mL, and the MIC of ciprofloxacin was >8 ?g/mL. These four strains were resistant to both tetracycline and ciprofloxacin by the disc-diffusion test and were exclusive of the three ceftriaxone-resistant strains. The majority of the isolates were obtained from children aged 0-5 year(s)70.3% (83 of 118) and 41.2% (14 of 34) were reported in 2010 and 2008 respectively. Since treating severe cases of cholera with antibiotics is important, the continuing spread of resistance in V. cholerae to the most important agents of therapy is a matter of concern. Also, chemoprophylaxis with antimicrobial agents is likely to become even more difficult. DOI: http://dx.doi.org/10.3329/jhpn.v30i1.11270 J HEALTH POPUL NUTR 2012 Mar;30(1):12-16